2003
DOI: 10.1093/ndt/gfg206
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of hypotensive side effects during online-haemodiafiltration and low temperature haemodialysis

Abstract: O-HDF showed a significant reduction of hypotensive episodes compared with HD. Surprisingly, o-HDF resulted in cooling of the blood via enhanced thermal energy losses within the extracorporeal system, despite use of replacement fluid prepared from pre-warmed dialysate. The incidence of symptomatic hypotension was reduced to that of o-HDF by using cooler Temp-HD. Thus, unexpected blood cooling appears to be the main blood pressure-stabilizing factor in o-HDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
88
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(101 citation statements)
references
References 17 publications
3
88
0
3
Order By: Relevance
“…This benefit of OL-HDF on intradialytic hypotension episodes has previously been described. 23,24 In addition, infection-associated mortality was also reduced by OL-HDF. ESRD patients have a significant risk of infectious complications, which represent the first cause of hospitalization and the second cause of death in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…This benefit of OL-HDF on intradialytic hypotension episodes has previously been described. 23,24 In addition, infection-associated mortality was also reduced by OL-HDF. ESRD patients have a significant risk of infectious complications, which represent the first cause of hospitalization and the second cause of death in hemodialysis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated similar benefits (28,29), although such findings are not universal (30,31). It seems that a cooling effect of the infusate may play a major role (31,32). There has been some concern that using the same dialysis fluid sodium level in online HDF and HD may result in sodium loading in the HDF group.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, it has been reported that the cold effect is still present in online HDF. 27 Our idea was to reproduce as closely as possible what physicians do in everyday clinical practice when using different techniques, independent of the pathophysiologic interpretation of the ISH; therefore, we decided not to give the investigators strict guidelines as to how to perform the treatments, Figure 2. 7.5% of all of the 28,950 sessions were complicated by ISH.…”
Section: Discussionmentioning
confidence: 99%